Răspuns :
a) a³ - ab² = a(a² - b²) = a(a-b)(a+b)
b) (x²+5)²-6(x²+5)=(x²+5) [(x²+5) - 6] = (x²+5)(x²-1)=(x²+5)(x-1)(x+1)
c) (x²+y²)²-4x²y² = (x²)² + 2x²y² + (y²)² - 4x²y² = (x²)² + (y²)² -2x²y² = (x²-y²)²=
= (x²-y²)(x²-y²)=(x²-y²)(x-y)(x+y)
In plus, la c), daca vrei sa continuam egalitatea, se poate scrie ca un produs de 4 factori. Adica: =(x-y)(x+y)(x-y)(x+y).
b) (x²+5)²-6(x²+5)=(x²+5) [(x²+5) - 6] = (x²+5)(x²-1)=(x²+5)(x-1)(x+1)
c) (x²+y²)²-4x²y² = (x²)² + 2x²y² + (y²)² - 4x²y² = (x²)² + (y²)² -2x²y² = (x²-y²)²=
= (x²-y²)(x²-y²)=(x²-y²)(x-y)(x+y)
In plus, la c), daca vrei sa continuam egalitatea, se poate scrie ca un produs de 4 factori. Adica: =(x-y)(x+y)(x-y)(x+y).